Improving wasting among children under-5 years in Malawi: The role of farm input subsidies - Tione, Grace; Gondwe, Edith; Maonga, Beston B.; Machira, Kennedy; Katengeza, Samson Pilanazo (Frontiers in Public Health, 2022)
There is growing research interest to understand social welfare linkages between farm input subsidies and nutritional status of beneficiaries among several countries, especially in Sub-Saharan Africa. In this study, we contribute to this body of literature by assessing the role of the Farm Input Subsidy Program (FISP) in Malawi on nutrition outcomes of vulnerable groups such as under-five children. We examine the link between FISP and child wasting. We assume that FISP increases Maize (starch) and legume (fats and protein) production, which potentially improves under-five children's nutrition status such as wasting. The study hypothesize that FISP increases dietary diversity through food availability and accessibility at the household level, thereby reducing child wasting measured by weight for height (WHZ). We used Malawi's Integrated Household Panel Survey data (IHPS) for 2013 and 2016 to study these relationships. This dataset is interesting because it captures a subset of FISP beneficiaries selected using revised selection criteria to improve the program. We employ a two-stage least squares approach to run a Cobb Douglas production function and a correlated Random Effects (CRE) Model to account for endogeneity challenges and an unbalanced panel dataset. The findings suggest that FISP beneficiaries were associated with significant increases in maize and legume yields and subsequently improved food availability at the household level, which in the short term decreased the levels of wasting among the under-five children. These findings suggest that input subsidies can enhance child nutrition status if properly managed.